A Double-Blind Randomized Placebo Controlled Trial of Thromboprophylaxis in Major Elective General Surgery Using Once Daily Injections of a Low Molecular Weight Heparin Fragment (Fragmin) - Ockelford, Paul A; Patterson, Janet; Johns, Allan S (Thrombosis and Haemostasis, 1989)
The safety and efficacy of the low molecular weight heparin fragment (Fragmin) administered as a single daily injection of 2,500 anti Xa units has been evaluated in 183 patients undergoing major elective general surgery. The study was double-blinded and placebo controlled. The active agent, or placebo, was given subcutaneously with the preoperative medication and continued postoperatively for 5-9 days. Ninety five patients received Fragmin and 88 were randomized to receive the placebo. The clinical characteristics of the two treatment groups were similar. Fragmin significantly reduced the incidence of deep venous thrombosis, as detected by a positive 125I fibrinogen leg scan, relative to the placebo treated patients (4/95, 4.2%; v. 14/88, 15.9%; p = 0.008). The thrombotic events occurred predominantly (73%) amongst patients with malignancy. Haemorrhagic endpoints necessitating discontinuation of the trial treatment were 4% in each group. No severe adverse reactions or drug related deaths occurred. These results indicate that 2,500 anti Xa units of Fragmin given only once daily is effective thromboprophylaxis for patients undergoing major elective abdominal surgery.
Keywords: Heparin; Low molecular weight heparin; Venous thrombosis prophylaxis; General surgery; Randomized trial